1964
DOI: 10.1139/v64-197
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic Spectra of Some Anionic Polymerization Systems

Abstract: The ultraviolet absorption spectra of living anionic polymerizing systems have been measured with sytrene, butadiene, and isoprene as the Inonolners; with lithium, sodium, arid potassiunl as the alkali metals; and with tetrahydrofuran, cyclohexane, and benzene as the solvents. For any rnononler the similarity of the spectra obtained with the various metals and solvents leads t o the conclusion that the alkali metal -carbon band has the same structure under the various conditions. From other evidence the bond i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
7

Year Published

1964
1964
2003
2003

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(17 citation statements)
references
References 11 publications
3
7
0
7
Order By: Relevance
“…Tobolsky has, however, reported before that little change in microstructure occurred after the abrupt change caused by the first sinall addition of tetrahydrofuran. The smoother change above is more in accord with the finding from ultraviolet studies of the polyisoprenyl carbanion forined in these systems (20). There appears to be very little change in the ionic nature of the carbon metal bond a s the solvent and the alkali metal are changed, and little reason to expect abrupt changes in microstructure.…”
Section: Polymer Microstrzlctzlresupporting
confidence: 75%
“…Tobolsky has, however, reported before that little change in microstructure occurred after the abrupt change caused by the first sinall addition of tetrahydrofuran. The smoother change above is more in accord with the finding from ultraviolet studies of the polyisoprenyl carbanion forined in these systems (20). There appears to be very little change in the ionic nature of the carbon metal bond a s the solvent and the alkali metal are changed, and little reason to expect abrupt changes in microstructure.…”
Section: Polymer Microstrzlctzlresupporting
confidence: 75%
“…This reaction has been noted previously with perchloric acid catalysis (6). Hence, very soon after the start of the reaction, the uv spectrum of the diphenylcarbenium ion is replaced slowly by that of the triphenylcarbenium ion.…”
Section: Resultssupporting
confidence: 71%
“…Because of the large extinction coefficient of poly(styryl)lithium ( ε = 1.3 × 10 4 L · mol −1 · cm −1 ) at λ max of 334 nm in benzene,37 the reaction was run under dilute conditions (e.g., 2.4 mL of styrene in 700 mL of toluene, and 0.55 mmol of sec ‐BuLi) in order to keep the absorbance below 1. Bywater et al37 reported that the maximum absorbance of the poly(styryl)lithium chain end is not highly dependent on the solvent. Therefore, it was expected that the maximum absorbance in toluene would be near the value reported for benzene.…”
Section: Resultsmentioning
confidence: 99%